ANALISIS BIBLIOMETRIK PERKEMBANGAN PENELITIAN DIGITAL GOVERNANCE - Pratama, Ryan Anggria; Setiawan, Azhari (Universitas Riau Kepulauan, 2024)
Abstract: Digital governance has been the subject of research in its evolution. Governments can use digital technology to enable citizens to participate in policy discussions, increase accountability, and improve democratic practices in government. Digital governance is increasingly receiving research attention because it involves managing and using digital technology in government practices. The database used in this research is the Scopus database. The keywords used in writing this scientific article are TITLE-ABS-KEY (